Forest management in southern China generates short term extensive carbon sequestration - Tong, Xiaowei; Brandt, Martin; Yue, Yuemin; Ciais, Philippe; Rudbeck Jepsen, Martin; Penuelas, Josep; Wigneron, Jean-Pierre; Xiao, Xiangming; Song, Xiao-Peng; Horion, Stephanie; Rasmussen, Kjeld; Saatchi, Sassan; et al. (Nature communications, 2020)
Land use policies have turned southern China into one of the most intensively managed forest regions in the world, with actions maximizing forest cover on soils with marginal agricultural potential while concurrently increasing livelihoods and mitigating climate change. Based on satellite observations, here we show that diverse land use changes in southern China have increased standing aboveground carbon stocks by 0.11 ± 0.05 Pg C y −1 during 2002–2017. Most of this regional carbon sink was contributed by newly established forests (32%), while forests already existing contributed 24%. Forest growth in harvested forest areas contributed 16% and non-forest areas contributed 28% to the carbon sink, while timber harvest was tripled. Soil moisture declined significantly in 8% of the area. We demonstrate that land management in southern China has been removing an amount of carbon equivalent to 33% of regional fossil CO 2 emissions during the last 6 years, but forest growth saturation, land competition for food production and soil-water depletion challenge the longevity of this carbon sink service. Forest management may play an important role in climate change mitigation. Here, Tong et al. combine remote sensing and machine learning modelling to map forest cover dynamics in southern China during 2002–2017, showing effects on carbon sequestration that are extensive but of uncertain longevity and possible negative impact on soil water.